Sustainable Urban Transport: Developing sustainability rankings and clusters based on an international comparison of cities. - Kenworthy, Jeffrey (Peter Lang Publishing, 2005)
The Millennium Cities Database for Sustainable Transport was developed over 3 years by Kenworthy and Laube for the International Union of Public Transport (UITP) in Brussels. It contains comprehensive, carefully checked standardised data on urban transport systems in 100 cities in developed and developing countries. The data cover a wide range of variables on private and public transport, urban form, transport infrastructure as well as a range of social, economic and environmental indicators of urban transport systems. The data are unique and allow thorough comparisons to be made of urban transport systems worldwide, especially levels of automobile dependence and the overall sustainability of passenger transport in different cities. The data and analyses in this paper present one approach to analysing key data from this database in order to understand the comparative sustainability of urban passenger transport in many cities around the world. Cities are ranked from the least to the most sustainable and clustered into groups in order to provide a better overview. An analysis is also presented to show how the value for each variable differs between these sustainable transport clusters in a more or less systematic way on a majority of the variables, suggesting that many of the key sustainability characteristics of cities are linked together in a synergistic or interdependent way.